P123 Review of patient characteristics and their association with survival in patients with copd on home non – invasive ventilation for hypercapnic respiratory failure: 5 year retrospective study. (15th November 2017) - Bleksley, JE; Ward, NR; Pritchard, R; Davidson, J; Hughes, PD; Palmer, J; Kathiresan, B
Abstract : Introduction: Home non-invasive ventilation (NIV) can improve outcomes in some patients with chronic obstructive pulmonary disease (COPD) and chronic hypercapnic respiratory failure. It remains unclear how to identify which patients will benefit most from this treatment. We have assessed patient characteristics and ventilator settings, and their association with survival, in individuals with COPD referred to our home NIV service Methods: Database and case notes of patients with COPD referred to our centre for home NIV between April 2011 and January 2017 were retrospectively analysed. We compared patient characteristics and ventilator settings in those who survived ≥12 months, to those who died earlier. Results: 150 patients were referred for home NIV. 41 patients did not tolerate NIV and discontinued treatment. Of the 109 who used NIV, 50 were alive in July 2017. Full data was available for 87 (58%) patients. Median survival in patients who used NIV (n=73) was 14.2 months (Interquartile Range (IQR) 3.2–28.8). In patients who discontinued NIV (n=14), survival was 21 months (IQR 5.2–38.2; p=0.81). Characteristics and NIV settings in the 79 patients who used NIV are shown in Table 1 . Discussion: 109 (73%) patients with COPD and hypercapnic respiratory failure continued using NIV after set up. Our data demonstrates lower body mass index was significantly associated with surviving<12 months after starting NIV. Patients who survived more than 12 months showed a non-significant trend to be male, younger and use NIV for more than 4 hours each night at higher inspiratory pressures. An unexpected finding was that patients intolerant of NIV showed a trend to longer survival, compared to those who continued with NIV. This may be due to the small number of patients with full data, or that 50% of these patients had stable hypercapnic respiratory failure at NIV initiation, compared to 25% in the patients who used NIV. Conclusions: These observations highlight the need for careful patient selection when considering which patients with COPD may benefit from home NIV, an awareness of the different features that may contribute to survival, and subsequent attention to ventilator settings and compliance once the treatment has begun.